Japanese New Religions in Brazil and the Dynamics of Globalization versus Glocalization - Shoji, Rafael (Journal of Religion in Japan, 2014)
Despite its tradition as a dominantly Christian country, Brazil is the host of the largest community of Japanese-descended people outside of Japan. This is the result of a long-lasting immigration process that started in 1908 and led to the establishment of a series of Japanese religions in the country. Although some of these groups are still restricted to the Japanese ethnic milieu, others have transcended their former ethnic boundaries and are quite successful in terms of recruiting new practitioners from a wider Brazilian audience. In order to identify the reasons for the failure or relative success of the various groups, the article starts with an overview of the historical development of Japanese religions in Brazil and summarizes the relevant results of the latest data provided by the institutions and the national census. The second part, which systematizes the strategies of transplantation of Japanese New Religions to Brazil, gives special attention to the construction of a transnational ancestor cult and the related emphasis on worldly benefits. The third part analyses in more detail the reinterpretation of ancestor worship and related rituals within Seichō-no-Ie. Finally, the fourth section refers the data to the academic discussion about the interrelated phenomena of globalization and glocalization.